PENGENALAN BANK SYARIAH PADA PESERTA DIDIK SEKOLAH DASAR NEGERI 067953 MEDAN - Ridwan, Muhammad; Syafina, Sherly (Publikasi Pengabdian Masyarakat, 2022)
This community service aims to introduce sharia banking to students of SDN 067953 Medan Deli subdistrict which is aimed at students in grades 4, 5 and 6. Sharia banking is a business entity whose activities are in the field of sharia finance and whose assets are in the form of finance and non-financial based on Islamic sharia principles. Every operational activity in it must not contain elements of usury or elements that are prohibited in Islam. Sharia banks aim to educate and guide people to think economically, behave in business and improve their quality of life by investing and carrying out sharia financing through sharia banks. By delivering material through lecture and discussion methods, we see the importance of introducing Islamic banking to students. The results of this service show that students understand sharia banking and have a great desire to save in sharia banks.